Decomposition-Based Optimization of Tailor-Made Green Diesel Blends - Phoon, L.Y.; Hashim, H.; Mat, R.; Mustaffa, A.A. (Computer Aided Chemical Engineering, 2017)
This chapter presents a tailor-made green diesel blends design algorithm to solve the tailor-made green diesel blends design problem. The design algorithm obtains the optimum solutions of tailor-made green diesel blends by incorporate experimental work with the decomposition-based computer-aided approach. There are four main phases in the algorithm: (1) formulate the design problem into a mathematical form; (2) optimize green diesel blend using a decomposition-based computer-aided approach; (3) further enhance the shortlisted blends using fuel additives and (4) experimental validation for the physicochemical properties and engine performance of the shortlisted green diesel blends. B5 palm oil biodiesel-biochemical blends is taken as a case study to demonstrates the application of the presented algorithm.